MOLECULAR MARKERS IN THE DIAGNOSIS OF PERIODONTAL DISEASE - Samistraro, Queila Da Luz; Locatelli, Claudriana; Baratto, César Milton (Anais eletrônicos do International Symposium on Science and Biotechnology, 2017)
Periodontal diseases are highly complex and have etiology multifactorial, with the participation of numerous biological mechanisms. This work aims to discuss some scientific research that uses molecular biology methods to evaluate periodontal disease. Several studies in the literature show that these tools can understanding the mechanisms involved in pathogenesis and the identification of new biomarkers of periodontal diseases, which can be used future diagnoses to detect the presence of active disease, to predict progression and evaluate the response to periodontal therapy. Several markers of lipid peroxidation, protein oxidation and DNA damage induced by reactive oxygen species can be measured in saliva or oral mucosa. Clinical studies have shown an association with oral pathologies at least for some of the established salivary markers of oxidative stress. The results showed an important correlation between oxidative stress biomarkers and periodontal disease.